CORRELATION OF AMNIOTIC FLUID INDEX VALUES WITH MATERNAL AND PERINATAL OUTCOMES IN PRETERM PREMATURE RUPTURE OF MEMBRANES. - Priya, Vamsi; Hasamnis, Varada; Vaidehi, Munukutla (Student’s Journal of Health Research Africa, 2025)
Background: Preterm Premature Rupture of Membranes (PPROM) is a significant obstetric complication associated with adverse neonatal outcomes. This study aims to evaluate the relationship between Amniotic Fluid Index (AFI) levels and clinical outcomes in patients with PPROM between 26–36 weeks of gestation. Methods: A cohort of 100 patients diagnosed with PPROM between 26–36 weeks of gestation were analyzed. Demographic data, gestational age, AFI levels, and clinical outcomes including chorioamnionitis, neonatal sepsis, respiratory distress syndrome (RDS), and neonatal survival were recorded. Statistical analysis was conducted to assess the associations between AFI levels and these clinical outcomes. Results: The study population consisted of 80% patients with gestational ages between 32–36 weeks and 20% between 26–31 weeks. The majority (49%) had an AFI <5. Chorioamnionitis was present in 50%, and neonatal sepsis occurred in 68% of neonates. Neonatal survival was observed in 93% of cases. Gestational age was inversely correlated with AFI (P < 0.001), with lower gestational age associated with AFI <5. No significant association was found between AFI and chorioamnionitis or neonatal sepsis. AFI <5 was significantly associated with an increased risk of RDS (P = 0.003) and neonatal death (P = 0.005), with an odds ratio of 3.78 for RDS in patients with AFI <5. Chorioamnionitis was associated with neonatal sepsis (P = 0.005). Conclusion: Low AFI (<5) in patients with PPROM is significantly associated with adverse neonatal outcomes, including respiratory distress syndrome and neonatal death. Gestational age and AFI levels play crucial roles in predicting neonatal survival and complications. Monitoring AFI can help identify high-risk pregnancies requiring closer observation and management. Recommendations: Healthcare providers should monitor AFI regularly in PPROM cases, especially with low AFI (<5). Enhanced neonatal surveillance for RDS and other complications is crucial. Early interventions and NICU preparation, particularly for gestational age <32 weeks,